2017
DOI: 10.1177/0897190017698057
|View full text |Cite
|
Sign up to set email alerts
|

Clinic-Level Population Health Intervention by PGY2 Ambulatory Care Pharmacy Residents to Optimize Medication Management in a Self-Insured Employer Health Plan Population

Abstract: PGY2 residents identified and resolved numerous clinically relevant MRPs. Patient-specific criteria can be utilized to target self-insured employer health plan patients who are likely to have clinically relevant MRPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…After preliminary screening, 250 articles needed to be further screened. Twenty-seven articles ( Patel et al, 2005 ; Gisev et al, 2009 ; Gomez et al, 2009 ; Hooper et al, 2009 ; Zhao, 2012 ; Roth et al, 2013 ; Lenander et al, 2014 ; Nadir et al, 2014 ; Tan et al, 2014 ; Mendonca et al, 2016 ; Okumura et al, 2016 ; Rodis et al, 2017 ; Schwartz et al, 2017 ; Benson et al, 2018 ; Vande Griend et al, 2018 ; Yang et al, 2018 ; Hazen et al, 2019 ; Khera et al, 2019 ; Neves et al, 2019 ; Santos et al, 2019 ; Zhang et al, 2020a ; Zhang et al, 2020b ; Chung et al, 2020 ; Gerard et al, 2020 ; Puspitasari et al, 2020 ; Samir Abdin et al, 2020 ; Troncoso-Marino et al, 2020 ) were finally included (there were only 26 studies because one of the studies was reported in two articles) ( Zhang et al, 2020a ; Zhang et al, 2020b ). The process of study selection is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After preliminary screening, 250 articles needed to be further screened. Twenty-seven articles ( Patel et al, 2005 ; Gisev et al, 2009 ; Gomez et al, 2009 ; Hooper et al, 2009 ; Zhao, 2012 ; Roth et al, 2013 ; Lenander et al, 2014 ; Nadir et al, 2014 ; Tan et al, 2014 ; Mendonca et al, 2016 ; Okumura et al, 2016 ; Rodis et al, 2017 ; Schwartz et al, 2017 ; Benson et al, 2018 ; Vande Griend et al, 2018 ; Yang et al, 2018 ; Hazen et al, 2019 ; Khera et al, 2019 ; Neves et al, 2019 ; Santos et al, 2019 ; Zhang et al, 2020a ; Zhang et al, 2020b ; Chung et al, 2020 ; Gerard et al, 2020 ; Puspitasari et al, 2020 ; Samir Abdin et al, 2020 ; Troncoso-Marino et al, 2020 ) were finally included (there were only 26 studies because one of the studies was reported in two articles) ( Zhang et al, 2020a ; Zhang et al, 2020b ). The process of study selection is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, 61.54% ( n = 16) were from developed countries, including six from America ( Patel et al, 2005 ; Roth et al, 2013 ; Rodis et al, 2017 ; Schwartz et al, 2017 ; Vande Griend et al, 2018 ; Chung et al, 2020 ), three from Canada ( Khera et al, 2019 ; Gerard et al, 2020 ; Samir Abdin et al, 2020 ), three from Australia ( Gisev et al, 2009 ; Tan et al, 2014 ; Benson et al, 2018 ), two from Spain ( Gomez et al, 2009 ; Troncoso-Marino et al, 2020 ), one from the Netherlands ( Hazen et al, 2019 ), and one from Sweden ( Lenander et al, 2014 ); 38.46% ( n = 10) were from developing countries, including four from Brazil ( Mendonca et al, 2016 ; Okumura et al, 2016 ; Neves et al, 2019 ; Santos et al, 2019 ), three from China ( Zhao, 2012 ; Yang et al, 2018 ; Zhang et al, 2020a ; Zhang et al, 2020b ), two from Qatar ( Hooper et al, 2009 ; Nadir et al, 2014 ), and one from Indonesia ( Puspitasari et al, 2020 ). According to the types of study design reported by the authors, there were six prospective studies ( Hooper et al, 2009 ; Roth et al, 2013 ; Rodis et al, 2017 ; Benson et al, 2018 ; Yang et al, 2018 ; Zhang et al, 2020a ; Zhang et al, 2020b ), five cross-sectional studies ( Zhao, 2012 ; Nadir et al, 2014 ; Okumura et al, 2016 ; Hazen et al, 2019 ; Troncoso-Marino et al, 2020 ), four retrospective studies ( Mendonca et al, 2016 ; Vande Griend et al, 2018 ; Chung et al, 2020 ; Gerard et al, 2020 ), five before-and-after controlled or longitudinal studies ( Gomez et al, 2009 ; Tan et al, 2014 ; Khera et al, 2019 ; Neves et al, 2019 ; Samir Abdin et al, 2020 ), and one rand...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations